The impact of tourism on the Ometepe Island Biosphere Reserve, Nicaragua - Serra Vazquez, Luis H. (2025)
The objective of this article is to analyze the impacts that the tourism boom has had on the Ometepe Island Biosphere Reserve and identify the challenges to promote sustainable ecotourism. The study is based on a qualitative methodology with interviews to key informants and direct observation carried out in the second half of 2023. The results highlight positive effects of tourism in boosting the economy and generating income, but questionable effects in the cultural and environmental spheres.